Substrate integrated waveguide bandpass filter for short range device application using rectangular open loop resonator - Dian Widi Astuti; Rizki Ramadhan Putra; Muslim Muslim; Mudrik Alaydrus (Institute of Advanced Engineering and Science, 2021)
The substrate integrated waveguide (SIW) structure is the candidate for many application in microwave, terahertz and millimeter wave application. It because of SIW structure can integrate with any component in one substrate than others structure. A kind components using SIW structure is a filter component, especialy bandpass filter. This research recommended SIW bandpass filter using rectangular open loop resonator for giving more selectivity of filter. It can be implemented for short range device (SRD) application in frequency region 2.4 - 2.483 GHz. Two types of SIW bandpass filter are proposed. First, SIW bandpass filter is proposed using six rectangular open loop resonators while the second SIW bandpass filter used eight rectangular open loop resonators. The simulation results for two kinds of the recommended rectangular open loop resonators have insertion loss (S21 parameter) below 2 dB and return loss (S11 parameter) more than 10 dB. Fabrication of the recommended two kind filters was validated by Vector Network Analyzer. The measurement results for six rectangular open loop resonators have 1.32 dB for S21 parameter at 2.29 GHz while the S11 parameter more than 18 dB at 2.26 GHz – 2.32 GHz. While the measurement results has good agreement for eight rectangular open loop resonators. Its have S21 below 2.2 dB at 2.41 – 2.47 GHz and S11 16.27 dB at 2.38 GHz and 11.5 dB at 2.47 GHz.